SIKAP MASYARAKAT TERHADAP PENERIMA BANTUAN BERAS SEJAHTERA (RASTRA) DI DESA TULE KECAMATAN MELONGUANE TIMUR KABUPATEN KEPULAUAN TALAUD - Charolina Anci Parapaga; Zoni Henki Singal; V. E. T. Salem (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2020)
Rastra is a government program to play the true function of the state for the food security of its people. This program seeks to meet the people's food availability so that there are no more people who go hungry due to lack of access to food. This program aims to reduce the expenditure burden of Target Households (RTS) through the fulfillment of part of their basic needs in the form of rice, but the response of the Tule Village community is that some give good responses but some cannot accept it. The Rasta Program is one of the poverty reduction and social protection programs in the food sector organized by the Central Government in the form of subsidized rice assistance to low-income households (poor and vulnerable to poor households).